Therapeutic effect and safety of individualized chemotherapy combined with sequential immunotherapy based on BRCA1 mRNA expression level in unresectable pancreatic cancer - Du, Juan; Zhu, Linxi; Sha, Huizi; Zou, Zhengyun; Shen, Jie; Kong, Weiwei; Zhao, Lianjun; Gu, Qing; Yu, Lixia; Qiu, Yudong; Liu, Baorui (Frontiers in Oncology, 2022)
Aim: We aimed to evaluate the efficacy and safety of individualized chemotherapy combined with sequential immunotherapy based on BRCA1 mRNA expression in the treatment of unresectable pancreatic cancer. Methods: The expression of BRCA1 mRNA in tumor tissues of patients with pancreatic cancer was detected. According to the expression level, gemcitabine + nab-paclitaxel chemotherapy or gemcitabine + oxaliplatin chemotherapy combined with sequential GM-CSF and IL-2 immunotherapy was applied. Patients’ conditions，treatment efficacy and safety were assessed every 4 cycles. Results: A total of 25 patients were enrolled in the study. All of them were observed for toxic side effects and 24 of them were evaluated for efficacy. The median overall survival and median progression-free survival were 11.9 months and 6.3 months. The disease control rate was 91.7%, of which 37.5% (9/24) patients achieved partial remission (PR), 54.2% (13/24) patients achieved stable disease (SD) and 8.3% (2/24) patients were assessed as progressive disease(PD). Of the 15 patients with medium or high expression in BRCA1 mRNA, 7 achieved PR and 8 achieved SD. Of the 9 patients with low BRCA1 mRNA expression, 2 achieved PR, 5 achieved SD and 2 had PD. The proportion of eosinophils in the blood of some patients with good therapeutic effects was significantly higher than that before treatment. Hematological and non-hematological toxicity during the treatment were mostly grade 1~2. The two most common grade 3 to 4 adverse events were fever and thrombocytopenia. Conclusion: Our results suggest that individualized selection of chemotherapy combined with sequential immunotherapy according to BRCA1 mRNA expression level in the treatment of unresectable pancreatic cancer have curative effect and controllable adverse reactions. The improvement of treatment efficiency may be related to the activation of non-specific immune response, which is worthy of further clinical discussion and application.